Elementary school children and singing during the [COVID-19] pandemic: collective songwriting in remote classes (Orfeu, 2021)
Based on Sociology of Childhood studies, this paper intends to analyze the songs written by 3rd to 5th graders from a private school in São Paulo, Brazil. These songs were written in the context of Covid-19 pandemic, which submitted those students to take classes remotely. By understanding music as a game, this article also discuss the poetic and musical shapes as a luddic path that children have created to sort this world wide unfavorable situation they were going through. Their compositions bring to light both their way to make music and how they capture and (re)create their living contexts and relationships.
Keywords: Musical composition; Covid-19; Children; Sociology of childhood